1988
DOI: 10.1002/ccd.1810140302
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and electrocardiographic consequences of high‐ and low‐osmolality contrast agents for left ventricular angiography

Abstract: The cardiovascular effects of two nonionic contrast agents with low osmolality (iohexol and metrizamide) were compared with one standard ionic, high-osmolality contrast agent (metrizoate) used for left ventricular (LV) angiography in patients with coronary heart disease. Metrizoate induced a marked elevation of LV end-diastolic pressure and LV systolic pressure and an increase in cardiac output after a delay of a few minutes. All these changes were significantly less severe with iohexol and metrizamide. Hypote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Similar pressure increases have been described by several authors for lowosmolar contrast agents [5,10,12,31,38]. The immediate and simultaneous decreases in left ventricular systolic pressure, aortic pressures and systemic vascular resistance are consistent with a rapid and transient vasodilatory effect of contrast agents that has been shown in several studies [1,2,4].…”
Section: Other Hemodynamic Variablessupporting
confidence: 68%
See 2 more Smart Citations
“…Similar pressure increases have been described by several authors for lowosmolar contrast agents [5,10,12,31,38]. The immediate and simultaneous decreases in left ventricular systolic pressure, aortic pressures and systemic vascular resistance are consistent with a rapid and transient vasodilatory effect of contrast agents that has been shown in several studies [1,2,4].…”
Section: Other Hemodynamic Variablessupporting
confidence: 68%
“…Several mechanisms have been proposed for the contrast-induced increase in LVEDP, such as expansion of the plasma volume, depression of contractility, decreased myocardial compliance, and an increased arterial pressure that may be due to a reflex sympathetic stimulation [4,10,36]. It is more likely that systemic rather than myocardial effects are involved, because Mancini et al, found no increase in LVEDP during coronary angiography even with high-osmolar contrast media [37].…”
Section: Main Trial Parameter: Lvedpmentioning
confidence: 93%
See 1 more Smart Citation